Focusing error detection based on astigmatic method with a double cylindrical lens group. (October 2018) - Bai, Zhen; Wei, Jingsong
Highlights: An astigmatic method with two cylindrical lenses is proposed. A theoretical analysis and simulation are carried out. A focusing error detection system is established. The linear tracking range is up to 18  μ m . The tracking accuracy is approximately 50 nm. Abstract: Autofocusing and autotracking are widely used in maskless laser lithography, optical imaging, and recording and readout of optical information storage. With the development of optoelectronic techniques, the accuracy of autofocusing and autotracking thus needs to be improved to the nanoscale, and the autotracking range also needs to be extended to tens of micrometers. In this work, an astigmatic method with two cylindrical lenses is proposed, where the focusing error signal is extracted to detect the focusing error. A theoretical analysis and simulation are carried out, accordingly. A focusing error detection system is established to demonstrate the theoretical analysis. The experimental results indicate that the focusing error signal curves present good "S" characteristics. The linear tracking range is up to 18  μ m, and the tracking accuracy is approximately 50 nm. The theoretical and experimental results indicate that the astigmatic method with two cylindrical lenses is a good method for autofocusing and autotracking with both high accuracy and large dynamic range. This work is useful in the fields of high-resolution maskless laser lithography and optical imaging.